PENGARUH KEPEMIMPINAN, MOTIVASI, DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA PEGAWAI KANTOR PERTANAHAN KOTA SEMARANG - Sarwindah, 13.05.51.0023; Indriyaningrum, Kis (Students Journal of Economic and Management, 2017)
The purpose of this study was to analyze the influence of leadership, motivation and organizational commitment to employee performance of Semarang City Land Office. The population in this study is the Employee of the Land Office of Semarang are still active a total of 219 people. The sample in this study as many as 69 people. The sampling technique using simple random sampling. The analysis tool used is multiple linear regression. The results of the analysis can be concluded that: Leadership positive and significant influence on employee performance. Motivation positive and significant impact on employee performance. Organizational commitment and significant positive effect on employee performance Keywords: leadership, motivation, organizational commitment and employee performance